What makes A. guillouiae SFC 500-1A able to co-metabolize phenol and Cr(VI)? A proteomic approach - Ontañon, Ornella Mailén (2018)
Acinetobacter guillouiae SFC 500-1A is an environmental bacterium able to efficiently co-remediate phenol and Cr(VI). To further understand the molecular mechanisms triggered in this strain during the bioremediation process, variations in the proteomic profile after treatment with phenol and phenol plus Cr(VI) were evaluated. The proteomic analysis revealed the induction of the β-ketoadipate pathway for phenol oxidation and the assimilation of degradation products through TCA cycle and glyoxylate shunt. Phenol exposure increased the abundance of proteins associated to energetic processes and ATP synthesis, but it also triggered cellular stress. The lipid bilayer was suggested as a target of phenol toxicity, and changing fatty acids composition seemed to be the bacterial response to protect the membrane integrity. The involvement of two flavoproteins in Cr(VI) reduction to Cr(III) was also proposed. The results suggested the important role of chaperones, antioxidant response and SOS-induced proteins in the ability of the strain to mitigate the damage generated by phenol and Cr(VI). This research contributes to elucidate the mechanisms involved in A. guillouiae SFC 500-1A tolerance and co-remediation of phenol and Cr(VI). Such information may result useful not only to improve its bioremediation efficiency but also to identify putative markers of resistance in environmental bacteria.